"Schumpeterianism" Revised: The Critique of Elites in Capitalism, Socialism and Democracy. Issue 4 (2nd October 2017) - Piano, Natasha
ABSTRACT: A close reading of Capitalism, Socialism and Democracy underscores Schumpeter's critique of elite political capacities. Given the neglect of this critique in contemporary scholarship, it might warrant a revision of our understanding of "Schumpeterianism." To notice the critique of elites, we need to read Part IV in the context of the work as a whole, and with greater sensitivity to the sarcasm, irony, and humor that permeate the book. Such a reading produces a fundamentally altered understanding of Schumpeter's contribution to democratic theory.